An investigation of Facebook boredom phenomenon among college students. Issue 4 (16th November 2015) - Yazdanparast, Atefeh; Joseph, Mathew; Qureshi, Anita
Abstract : Purpose: – The purpose of the paper is to provide an initial understanding of the factors influencing and emanating from Facebook boredom. Specifically, the study addresses important issues such as reasons for liking and disliking Facebook, Facebook users' boredom states with this social networking site, factors associated with Facebook boredom and impact of boredom on the success and effectiveness of social marketing activities. Design/methodology/approach: – A paper and pencil questionnaire was administered to undergraduate students at two local universities in exchange for course credit. Survey questions were adapted from previously validated scales, and measurement adaptations were minimal and only related to the context of questions to assure their relevance with the context of our study. Bootstrapping technique, Sobel test, ANOVA and regression techniques were used to test the hypotheses and address research questions. Findings: – The results indicate that both genders are experiencing Facebook boredom and spend less time on Facebook. Moreover, Facebook boredom negatively impacts users' attitudes toward this social networking site, which in turn impact attitudes towards ads on Facebook. This observation reveals an important point regarding the necessity of studying the phenomenon of Facebook boredom for marketers. Also, the findings indicate that age is an important factor impacting users' level of boredom with Facebook, as younger users report significantly higher levels of Facebook boredom as compared to older users. Research limitations/implications: – To capture the opinion of Facebook users, this study used a sample of college students at two universities which may not be representative of the entire population of Facebook users. Much of the existing research on Facebook, however, has focused on undergraduate college students and is primarily based on studies utilizing the undergraduate population. Originality/value: – This is the first study to empirically examine the phenomenon of Facebook boredom by linking major theories of boredom with uses and gratification theory. The results add to the extant literature by identifying the underlying mechanism through which boredom with social media impacts effectiveness of social media marketing activities. The results shed more light on the consequences of Facebook boredom for digital marketers and reveal that age is an important factor in Facebook boredom.